The instant in Plato - Carvajal Correa, Carlos Alberto (Estudios de Filosofía, 1990)
Within the setting of the hypothetical game in the dialog of Parmenides, where the possibilities of the One and the Many are examined in relation to their participation in being, there appears, as a condition for the participation mentioned in different times, the existension of the instant. This element irrupts, fractioning the continuity of the magnitude of movement, thus introducing "change" as the concept that permits evading a contradiction in which the One might fall, by simultaneously participating and not participating. The circunstances of the thematical apparition of the instant in the dialog are thus exposed, with its untemporal trait being an outstanding characteristic there of.